Manajemen kesejahteraan di antara guru pendidikan jasmani pra-layanan selama pandemi - Aguirre, Francisco (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2022)
Due to a number of circumstances, such as heightened societal pressure, a lack of proper safety measures, and an emotionally taxing setting where many patients are suddenly dying, alone and afraid, the COVID-19 pandemic is having adverse effects on people's well-being. Despite the current circumstances, it is critical that learning continues in this unpredictable context. In an effort to aid students' well-being and development, the researcher analyzed the ability to manage one's well-being, especially in this pandemic for students enrolled in physical education. Materials and methods. This study was conducted to assess the management of the well-being of pre-service physical education teachers at the Batangas State University JPLPC-Malvar campus during the pandemic with the goal of determining the implications for physical education. This study utilized descriptive–correlational research using a questionnaire as the primary tool for gathering quantitative data, which was subjected to statistical analysis by employing frequency and percentage, mean and standard deviation, and chi-square. Results. From the data collected, well-being during the pandemic is considerably managed in terms of feeling pleased, appreciative, and proud when completing assigned responsibilities. Sex and socioeconomic position are considerably associated with the respondent's well-being management during the pandemic. Results show that based on the respondent's assessment of their well-being, it was highly managed; therefore, a proposed program to fully strengthen and revitalize the management of well-being should be implemented and included in the teaching process of physical health and wellness for pre-service physical education teachers.